STUDENT LOANS: AN ALTERNATIVE TO FINANCE STUDIES USED BY HIGHER EDUCATION STUDENTS IN MOZAMBIQUE - Joaquim, José Amilton; Cerdeira, Luísa; Cossa, Eugénia Flora Rosa (International Journal of Research -GRANTHAALAYAH, 2023)
Student loans as an alternative to social support for students are a contribution of economic theory to the financing of higher education. This study seeks to reflect on loans as a social support policy used by several countries for higher education students and to show the reality of loans made by higher education students in Mozambique. Data were collected from a questionnaire applied to higher education students, for a theoretical sample of 508 and an empirical sample of 607 students in the province of Gaza, in February and March 2018. Results reveal that student loans are not a social support policy co-financed by the Mozambican State, as in other contexts. Students have turned either to formal institutions, such as commercial and microfinance banks or to informal associations, called Xitique, to cover the costs of their studies. This allows concluding that, despite the challenges, loans can be a positive alternative for the government in the diversification of social support to students, which will allow better access to higher education, provided that they are introduced taking into account students/families’ socioeconomic conditions and with efficient mechanisms or systems that help control borrowers’ reimbursements and disbursements.